Titanium–salan‐catalyzed asymmetric sulfoxidations with H2O2: design of more versatile catalysts. (27th March 2013) - Talsi, Evgenii P.; Bryliakov, Konstantin P.
Abstract : Titanium–salan complexes with 3, 3'‐diphenyl substituents in the salicylidene rings of the salan ligand are efficient sulfoxidation catalysts, capable of catalyzing the asymmetric oxidation of bulky aryl benzyl sulfides with H2 O2 with good to high enantioselectivities. In this paper, substituent effects on titanium‐salan‐catalyzed enantioselective oxidation of sulfides to sulfoxides have been systematically investigated. Titanium–salan catalysts with halogen substituents at the 5, 5'‐positions (3, 3'‐H2 dihydrogen substituted) have been found to catalyze the oxidation of both bulky aryl benzyl sulfides and small alkyl phenyl sulfides with good to high enantioselectivities. Kinetic data witness a direct attack of the sulfide to the electrophilic active oxygen species; a consistent reaction mechanism is proposed. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Titanium‐salan complexes with halogen substituents at the 5, 5'‐positions are versatile catalysts for the oxidation of both bulky aryl benzyl sulfides and small alkyl phenyl sulfides, demonstrating good to high chemoselectivity (up to 92 %) and enantioselectivity (up to 93 % ee ).